Governance Capacity in Investment Management in Maros Regency - Akmal, Muh. Imaddudin; Hasniati, ‎; Ahmad, Badu (KnE Social Sciences, 2025)
Effective investment governance requires governance capacity that can accommodate the interests of various actors, regulate supportive regulations, and provide adequate resources. This study aims to analyze governance capacity in investment management in Maros Regency. This study uses a qualitative method with a case study approach, through in-depth interviews with key actors, field observations, and studies of regional investment policy documents. The stages of data analysis include data reduction, data presentation, and drawing conclusions. The results of the study show that in Maros Regency, the capacity of investment governance has been implemented quite well. Enabling rules of the game are reflected in regulations that support investment from the central government, but at the regional level there are no regulations that specifically regulate investment governance. Converging discourses are seen from the joint agreement between key actors in investment policy, including local governments, communities, and the private sector. Facilitating resources show adequate allocation of resources, such as funds and facilities, to support improving the quality of investment governance. However, there are challenges to be addressed, including coordination between government agencies that needs improvement.